Loved : how to rethink marketing for tech products - Lauchengco, Martina (Ascent Audio, 2022)
The best products can still lose in the marketplace. Why? They are beaten by stronger product marketing. Yet, product marketing is widely misunderstood. It includes segmenting and targeting customers, positioning products vs. alternatives, creating product collateral, and supporting sales teams. But great product marketing achieves much more: it identifies the best way to bring your product to market, accelerates your product's ability to penetrate markets over time, shapes what the world thinks about your product and your category, and inspires customers to tell your product's story. Loved explains the foundational principles of best-in-class product marketing for product teams, marketers, founders, and any leader with a product and a vision. The third book in the bestselling series including Inspired and Empowered, from Silicon Valley Product Group, Loved distills decades of lessons gleaned from working with hundreds of companies to show you: the centrality of product marketing to any product's success; the key skills and actions required to do it well; the four foundational principles of product marketing and how to implement them; how to hire, lead, and organize product marketing; how product marketers optimize crucial collaboration with other functions; and tools and agile marketing practices that help simplify and elevate product marketing.